The insulator-superconductor transformation in cuprates - Edwards, P; Mott, N; Alexandrov, A (1998)
We model the layered cuprates as doped 2D semiconductors with (bi)polaronic carriers partly localized by disorder. The composition-induced transition to the superfluid Bose-liquid state takes place without any intermediate, classical 'metallic' regime. The Mott criterion, highly successful in conventional doped semiconductors and related fermion systems (e.g. expanded metals), should now be appropriate for bosons. On this view, the transition to the metallic state will be coincident with the Bose condensation to the superconducting state. © 1998 Plenum Publishing Corporation.